2013
DOI: 10.1186/1471-2164-14-557
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional analysis of abdominal fat in genetically fat and lean chickens reveals adipokines, lipogenic genes and a link between hemostasis and leanness

Abstract: BackgroundThis descriptive study of the abdominal fat transcriptome takes advantage of two experimental lines of meat-type chickens (Gallus domesticus), which were selected over seven generations for a large difference in abdominal (visceral) fatness. At the age of selection (9 wk), the fat line (FL) and lean line (LL) chickens exhibit a 2.5-fold difference in abdominal fat weight, while their feed intake and body weight are similar. These unique avian models were originally created to unravel genetic and endo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
85
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(93 citation statements)
references
References 120 publications
7
85
0
1
Order By: Relevance
“…Moreover, FDPS, NSDHL and FDFT1 are candidate genes to regulate fat deposition in chickens: excessive fat deposition in chickens is associated with negative effects on poultry production, in terms of feed efficiency [70]. It has also been reported that FDPS, NSDHL and FDFT1 are up regulated in the fat line chickens and in liver and adipose tissue in fast growing chickens [71,72].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, FDPS, NSDHL and FDFT1 are candidate genes to regulate fat deposition in chickens: excessive fat deposition in chickens is associated with negative effects on poultry production, in terms of feed efficiency [70]. It has also been reported that FDPS, NSDHL and FDFT1 are up regulated in the fat line chickens and in liver and adipose tissue in fast growing chickens [71,72].…”
Section: Discussionmentioning
confidence: 99%
“…(NA: BWA did not detect any BAM alignment across the reference provided.) [17,[42][43][44][45][46][47][48][49][50][51][52][53][54][55][56][57][58][59][60] analyzing sequencing data derived from PacBio RS II and Illumina MiSeq sequencing technologies. The only difference detected in our assembled locus sequence relative to the Gallus Gallus (v5) is a 5 bp insertion in the intronic region of chIFITM3.…”
Section: Discussionmentioning
confidence: 99%
“…This gene is associated with increased glycerol production, leading to an accumulation of fat, and was found in a previous study to be expressed at higher levels in chickens selected for low abdominal fat content (Resnyk et al . ). However, there were no obvious candidate genes in the zero‐diversity regions.…”
Section: Discussionmentioning
confidence: 97%